Demographic and clinical characteristics associated with a history of bizarre delusions in a cross-diagnostic sample of individuals with psychotic disorders - (:unkn) unknown (ELSEVIER SCIENCE BV, 2018)
Bizarre delusions (BizD) are not specific to schizophrenia (SZ) and can be found in other psychotic disorders. However, to date, there are no studies investigating socio-demographic and clinical characteristics associated with BizD across the psychosis spectrum. In this study 819 subjects with a diagnosis of SZ (n= 250), schizoaffective disorder (SZA) (n= 228) and bipolar I disorder (BD) (n= 341) were included. Patients with history of BizD and with no BizD were compared with respect to socidemographic and clinical variables, and predictors of BizD were explored. Patients with BizD were less educated, less likely to be married, had higher Positive and Negative Syndrome Scale (PANSS) negative scores and lower Young Mania Rating Scale scores. Younger age, SZ and SZA diagnoses, higher PANSS positive scores, presence of reference delusions, tactile and olfactory hallucinations were predictors. Our results indicate that BizD are associated with higher illness severity, lower functionality and specific set of symptoms.
Keywords: Schizophrenia; Bipolar disorder; Tactile; Olfactory; Hallucination; SCHNEIDERIAN 1ST-RANK SYMPTOMS; 1ST RANK SYMPTOMS; SCHIZOPHRENIA; HALLUCINATIONS; DEFINITION; PREDICTION; FREQUENCY; ADMISSION; ILLNESS; DSM-5